A reflection on borrowing from western economics. Issue 2 (13th December 2019) - Fang, Fuqian
Abstract : Purpose: Western economics came into being with the rise of the capitalist market economy. It had a nature of duality beginning from its birth: the justificativeness of providing theoretical pillars for the capitalist market economy system and the scientificity of revealing the internal relations and operating rules of the capitalist market economy. The paper aims to discuss this issue. Design/methodology/approach: However, after the 1830s, this justificativeness gradually evolved into vulgarity. Since the 1930s, modern western mainstream economics has mainly explored the general market economy on the assumption that the capitalist system remains unchanged, and many outcomes of such research are positive and beneficial. Findings: Political economy of socialism with Chinese characteristics, at the present stage, is mainly a Chinese socialist market economics. It is guided by the Marxist political economy and rooted in the great practice of China's reform and opening up and socialist modernization. Originality/value: According to political complexion, western economic theories can be divided into political economic theory, mainstream economic theory and basic economic theory. By subjecting these theories to what we term "elimination, " "transformation" and "transplantation" surgeries, respectively, we can absorb and accommodate their beneficial elements in building a political economy of socialism with Chinese characteristics, which in turn is conducive to the development and prosperity of such an economy.